Integrity: Human and Money - Suraya binti Wan Nik, Wan; binti Abdul Razak, Munira; binti Ali, Zuraina; Wei Xian, Kang; bin Mohd Ramli, Najmuddin (International Journal of Engineering and Technology, 2018)
Integrity, An Unseen Element That Can Make or Break Human Beings Through Monetary means is the gist of this first-hand observational research conducted by a student with the assistance of his lecturer. Observational research is a qualitative research method that employs the (direct and/or indirect) involvement of the researcher in the situation so as to gauge and identify what are the elements that need to be highlighted and is significant to the result as proof.Â The student was initially involved as the respondent but along the way he becomes the researcher (cum observer) looking into the situation or the study segment. Simultaneously, the observer also employs the ethnographic observational research method where all thoughts and opinions are written verbatim with minor grammar and structural amendments. The result is a clear-cut heartfelt observation that can be translated into a more quantified future research as a continuation of the present one.Â For clarification of the entire concept, the findings are tabulated to further emphasize the significance of integrity with regard to human and money. Using a newly created identifying scale (ID Scale) based on motivating and demotivating factors, we were able to â€˜seeâ€™ and appreciate the relationship changes as the result.Â Â Â